Dynamic Smile Evaluation Following Twin Block Appliance Therapy in Class II Division 1 Malocclusion - A Prospective Study - Navneet Singh; Tulika Tripathi; Saumya Kakkar; Priyank Rai; Isha Duggal (Indian Journal of Dental Research)
Background/Objectives: Smile analysis is a determinant tool for the assessment of orthodontic treatment outcome. This study aimed to evaluate and compare dynamic smile before and after twin block therapy. Materials and Methods: This prospective study was conducted on 30 subjects in age group of 11–14 years (mean age = 12.80 ± 1.2 years). Dynamic smile was recorded by videography at two time points, that is pre- (T0) and post- (T1) twin block therapy. Measurements were made on frontal rest and smile photographs. A paired t-test was used for comparison of changes at T0 and T1. P ≤ 0.05 was considered statistically significant. Results: At full smile, significant increase was observed in upper lip length (0.97 mm), lower lip length (1.96 mm) and thickness (0.52 mm), stomion inferius to supramentale (1.96 mm), lower lip to maxillary incisor (0.70 mm), distance from upper incisal edge to inferior portion of lower lip (1.73 mm), interlabial gap (1.26 mm), soft tissue lower facial height (3.59 mm), buccal corridor ratio (0.03), smile width (2.06 mm), maxillary intercanine width (3.61 mm) and width of all visible maxillary teeth (3.65 mm) following twin block therapy. Buccal corridor showed significant decrease (1.02–1.16 mm) post-twin block appliance therapy. At rest, statistically significant increase was observed in the upper lip length (1.60 mm), lower lip length (2.99 mm) and thickness (1.28 mm), stomion inferius-supramentale (4.47 mm) and soft tissue lower facial height (3.13 mm), whereas maxillary incisor exposure (2.09 mm) and interlabial gap (2.06 mm) showed significant decrease. Conclusions: Dynamic smile assessment revealed a significant improvement in smile aesthetics following twin block therapy.